2015
DOI: 10.4269/ajtmh.15-0045
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Forming Pneumonia Due to Staphylococcus aureus Following Dengue Fever

Abstract: Abstract. While visiting Malaysia, a 22-year-old previously healthy Japanese man developed myalgia, headache, and fever, leading to a diagnosis of classical dengue fever. After improvement and returning to Japan after a five day hospitalization, he developed productive cough several days after defervescing from dengue. Computed tomography (CT) thorax scan showed multiple lung cavities. A sputum smear revealed leukocytes with phagocytized gram-positive cocci in clusters, and grew an isolate Staphylococcus aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…In the present study, the most common pathogen in the 33 cases of confirmed bacteremia was Escherichia coli , followed by Staphylococcus aureus ( S aureus ), and streptococcus pp. Despite our finding that S aureus was the most commonly reported copathogen, different from that of other reports, [ 23 , 24 ] the present study and other reports [ 25 , 26 ] might indicate the clinical significance of bacterial infections in patients with severe dengue. It should at least emphasize the importance of an early diagnosis of cobacterial infections and prompt antibiotic treatment of patients critically ill with dengue.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the most common pathogen in the 33 cases of confirmed bacteremia was Escherichia coli , followed by Staphylococcus aureus ( S aureus ), and streptococcus pp. Despite our finding that S aureus was the most commonly reported copathogen, different from that of other reports, [ 23 , 24 ] the present study and other reports [ 25 , 26 ] might indicate the clinical significance of bacterial infections in patients with severe dengue. It should at least emphasize the importance of an early diagnosis of cobacterial infections and prompt antibiotic treatment of patients critically ill with dengue.…”
Section: Discussioncontrasting
confidence: 99%
“…Dengue patients are vulnerable to secondary bacterial infections due to leucopenia (especially neutropenia), impairment of antigen-presenting cells’ functions, reduction of the phagocytic and migratory capacities of macrophages, impairment of the interferon signaling pathway, impairment of the integrity of skin barrier against bacteria and other transient changes in the immune system caused by dengue virus [ 2 , 8 , 9 , 17 , 20 , 21 ]. Increased capillary leakage of DHF is also speculated to favor bacterial infections [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients might have both pneumonia and dengue and this problem might be difficult for diagnosis. The Staphylococcus pneumonia is reported for concurrence with dengue [4][5] . Cavity lesion is generally observed in those dengue with concurrent Staphylococcus pneumonia.…”
Section: Dengue and Pneumoniamentioning
confidence: 94%